Hubungan Faktor Social Area (Kebisingan), Faktor Individual Area (Karakteristik Individu), Dan Faktor Work Area (Beban Kerja Dan Hubungan Interpersonal) Terhadap Stres Kerja Pada Pekerja Departemen Spinning Di PT. Acryl Textile Mills, Tangerang Tahun 2024 - Aprilia Kurniawan, Fadillah; Saputra, Atang; Riyanto, Agus (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Work stress is a pressure that arises from the work environment and individual characteristics of workers that can affect the thought process, way of working, emotions and physical condition of a person. If work stress occurs at a high level and is not properly controlled, it can reduce worker productivity. Work stress can be influenced by several factors, including social area factors, individual area factors, and work area factors. This study aims to find out "The Relationship of Social Area Factors (Noise), Individual Area Factors (Individual Characteristics), and Work Area Factors (Workload and Interpersonal Relationships) to Work Stress in Workers of the Spinning Department at PT. Acryl Textile Mills, Tangerang in 2024". The discussions in this study are the social area (noise), individual area (age, education level, marital status, and working period), work area (workload and interpersonal relationships). This study is a type of analytical survey research in the form of a cross sectional study design. Data collection was carried out by measuring noise intensity and questionnaires in workers related to social area (noise), individual area (age, education level, marital status, working period), work area (workload and interpersonal relationships) in the Spinning Department at PT. Acryl Textile Mills. This study was analyzed using a statistical test using the Chi-square method. Based on the results of research from 81 workers in the Spinning Department of PT. Acryl Textile Mills, the results of workers who experienced work stress were obtained, namely, 67 workers (82.7%) experienced mild stress and 14 workers (17.3%) experienced moderate stress. Based on the results of bivariate analysis, it can’t be shown that there is a significant relationship between individual area factors (level of education) and work stress with p values (0.101) > 0.05.